THE IMPACT OF COMPLEX THERAPY ON QUALITY OF LIFE AND COGNITIVE IMPAIRMENT IN THE REHABILITATION OF PATIENTS WITH CHRONIC CEREBRAL ISCHEMIA - Максим Владимирович Авров; Валентина Михайловна Алифирова; Андрей Владимирович Коваленко (Medicina v Kuzbasse, 2018)
Subject. Methods and results of correction of quality of life and moderate cognitive impairment in patients with chronic cerebral ischemia. Objective. The study of the effectiveness of complex treatment in the correction of the quality of life index and cognitive impairment in patients with chronic cerebral ischemia.